Financial Sector Assessment : Chile - World Bank (World Bank, Washington, DC, 2013)
This Financial Sector Assessment (FSA) summarizes the FSAP report for Chile, with emphasis on structural and developmental issues. Chile's financial system is large, well diversified and resilient to shocks. Chile's exposure to sudden stops in capital flows is diminished under the current policy environment and rising international financial integration. The challenges faced by the financial system are mainly developmental. Greater competition in financial services will be key in facilitating a broader allocation of investable funds. The modernization of securities markets infrastructure is necessary to enhance liquidity. Reforms to the silo-based financial system oversight are required to enhance efficiency and risk management. The report looks at the following financial areas: financial structure; macroeconomic environment; macro-financial stability analysis; banking; corporate sector; insurance sector; pension funds; mutual funds; institutional investors and financing vehicles; securities markets liquidity, infrastructure, and oversight; hedges; financial oversight; and anti-money laundering.